Designing a Model for Reducing Behavioral Emotions through the Mindfulness of Social Security Organization Employees - Omolbanin Hassanloofard; Hassan Amiri; Korosh Parsa Moeen (مجله علوم پزشکی صدرا, 2000)
Introduction: The present study was conducted to present a model for reducing behavioral emotions through the mindset of Social Security employees.Methods: it is applied and developmental research in nature. The research method is mixed (qualitative-quantitative). This research used a non-random and snowball sampling method to collect the opinions of 30 participants (university professors and staff of the Social Security Organization) within three phases. The statistical population included all managers and employees of the Social Security Organization, which was about 420 people, of whom 200 people were selected as the sample size according to the Krejcie and Morgan Table. Also, the Fuzzy Delphi method was used to identify the components, and confirmatory factor analysis was used to determine the effect of the identified variables.Results: The results identified 76 themes and factors. Twelve sub-indices for behavioral emotions were classified in the form of variables, including descriptive observation, conscious deed, acceptance without judgment, and lack of reaction. Another 12 sub-indices for mindfulness were classified in the form of variables, including anger, anxiety, stress, fear, and sadness.  Conclusion: Considering high occupational tension and the Social Security Organization workplace, it is possible to reduce behavioral emotions by providing a calm and stress-free workplace for the staff.